Viola tovarii (Violaceae), a new species for Peruvian high Andes - Gonzáles, Paúl; Molina-Alor, Johanny (Phytotaxa, 2020)
We describe and illustrate Viola tovarii P. Gonzáles & J. Molina-Alor, a new species of Viola section Andinium from the high Andes of southwest Peru. Special emphasis is placed on the color and size of the flowers and leaves, style crest form, and presence or absence of stipules, which are key characters that were undervalued in previous taxonomic treatments dealing with this species assemblage. The species is illustrated and a photograph of the living plant is included.